Epidemiological and clinical features of rosacea in Korea: A multicenter cross‐sectional study. Issue 5 (25th March 2018) - Lee, Jee‐Bum; Moon, Jungyoon; Moon, Ki‐Rang; Yang, Ji Hoon; Kye, Young Chul; Kim, Kwang Joong; Kim, Nack In; Ro, Young Suck; Park, Kui Young; Park, Mi Youn; Song, Margaret; Ahn, Kyu Joong; et al.
Abstract: Rosacea is a common chronic inflammatory skin condition. Although several epidemiological and etiologic studies with large sample sizes have been conducted on Caucasians, such data regarding Asian populations are lacking. A total of 580 patients diagnosed with rosacea were enrolled from October 2014 to February 2015 at 14 general hospitals. Questionnaires, including the standard classification and grading system, were used for evaluation. The average age of the patients was 47.9 years. While 83.8% of patients revealed a single subtype, 16.2% of patients revealed mixed subtypes showing two or more subtypes simultaneously. Erythematotelangiectatic rosacea (ETR) was the most prevalent subtype. ETR combined with papulopustular rosacea showed the highest proportion in the mixed subtype group. Mild severity was revealed in 71.9% of patients. The most common aggravating factor was emotional changes (51.7%), followed by stress (48.4%). Approximately half of the patients (47.4%) showed relatively low awareness of rosacea. By identifying the epidemiological and etiologic features in Korea, we can suggest valuable clinical avenues for research, education and awareness among rosacea patients.